2021
DOI: 10.1101/2021.02.19.432029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Size of the Stag Determines the Level of Cooperation

Abstract: In the last 12,000 years, human societies have scaled up from small bands to large states of millions and even billions. Many modern societies and even groups of societies cooperate on large-scale projects with relatively low levels of conflict, but the scale and intensity of cooperation varies dramatically between societies. Here we attempt to formalize dynamics that may be driving this rapid increase in cooperation and the differences we see between societies. Our model extends an N-person stag hunt to inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We observe less overall incentive to cooperate as the cost 𝑐 increases (i.e., darker blue and has more area inside the triangles). This pattern resembles findings observed in human behavior, where the amount of cooperation depends on the size of the benefit compared to the cost [49]. Another observation is that defection is incentivized in the presence of any amount of self-focus (right axes), with the exception of one environment (𝑐 = 1 and 𝜈 = 0.5).…”
Section: Iterated Prisoner's Dilemma (Ipd)supporting
confidence: 81%
“…We observe less overall incentive to cooperate as the cost 𝑐 increases (i.e., darker blue and has more area inside the triangles). This pattern resembles findings observed in human behavior, where the amount of cooperation depends on the size of the benefit compared to the cost [49]. Another observation is that defection is incentivized in the presence of any amount of self-focus (right axes), with the exception of one environment (𝑐 = 1 and 𝜈 = 0.5).…”
Section: Iterated Prisoner's Dilemma (Ipd)supporting
confidence: 81%
“…Schnell et al [ 147 ] model the competition between cooperative groups at different scales, revealing the importance of resource availability to cooperation and competition. People cooperate to access resources that they would not be able to access by themselves or in a smaller group.…”
Section: Cultural Evolvability Applied To the Paradox Of Diversitymentioning
confidence: 99%
“…Clustered diversity may be optimal for avoiding homogeneity through conformity; dividing a problem to solve it [ 14 ]. By contrast, when the perception or reality of competition is zero-sum or resources are perceived to be limited, people cooperate at the scale needed to best access those limited resources, creating conflict and destructive competition [ 147 ]. This insight has policy implications.…”
Section: Resolving the Paradox Of Diversitymentioning
confidence: 99%
“…Previous modelling work has revealed complex evolutionary dynamics at work when the 2-person Stag–Hunt is generalised to a N-person game, specifically, scenarios of defector dominance, pure coordination, or coexistence may arise simultaneously if the population is assumed to be infinite, but when populations are finite and the population is the same size as the group, the evolutionary dynamics are profoundly affected, inverting the direction of natural selection ( Pacheco et al 2009 ). Building on this work Schnell and colleagues (under review ) showed that the size of the Stag reward further affected the level of cooperation in a N-person game such that when a new cooperation threshold is accessible to a population, the level of cooperation increases to reach this threshold. However, when the next threshold is out of reach, cooperation decreases as individuals refrain from costly cooperation.…”
Section: Introductionmentioning
confidence: 94%